Supraventricular arrhythmia in tetralogy of Fallot repair. (24th May 2021) - Vincze, V; Kardos, A; Kornyei, L; Balint, H
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Gottsegen National Cardiovascular Center BACKGROUND With aging morbidity related to arrhythmias in adult patients with Tetralogy of Fallot repair (TOFr) is increasing. OBJECTIVE We aimed to analyze the prevalence of supraventricular tachycardia in these patients using our prospective database. METHODS TOFr data were collected from our prospective database conducted since 2010. Supraventricular arrhythmias (intraatrial reentrant tachycardia (IART), atrial fibrillation, AFib) related complications and therapies were documented. RESULTS Among those with TOFr (n = 296, mean age 34 ± 11) supraventricular tachyarrhythmias (SVT) were present in 41 patients (14%), as following: n = 12 AFib, and n = 29 IART. At the univariate analysis predictors of atrial fibrillation and IART were: age at last follow-up (p < 0, 0001), age at first repair (p < 0, 0001), number of surgeries (p = 0, 014), and tricuspid regurgitation (p = 0, 013). Supraventricular tachycardia was a strong predictor of death (OR 3.0).  Twenty-five patients had radiofrequency ablation, and after a mean follow-up of 61 ± 56 months, the rate of recurrence for SVT was 32 %. In the non-ablated cohort (treated with amiodarone) 73 % recurrence was detected. CONCLUSION: Supraventricular arrhythmias are common in TOFr patients and are associated with increased mortality risk, but arrhythmia control with catheter ablation is superior to anti-arrhythmic drug therapy in this patient population.